Sexual size dimorphism and sex determination by morphometric measurements in locally adapted muscovy duck (Cairina moschata) in Nigeria - Abel Olusegun OGUNTUNJI; Kolawole Luke AYORINDE (Acta Agriculturae Slovenica, 2014)
Sexual size dimorphism (SSD) is a common phenomenon in most mammalian and poultry species. This study was undertaken to investigate SSD in nondescript locally adapted Muscovy ducks in Nigeria by applying descriptive analysis, sexual dimorphism index (SDI), sexual size dimorphism index (SSDI) and Principal Component analysis to morphological variables. Besides, attempt was made to identify best morphological predictors of sex using Stepwise Discriminant analysis. Data on ten morphological traits; body weight, body girth, body length, wing length, shank length, shank circumference, thigh length, total leg length, bill length and bill width were taken from 1,020 extensively managed adult Muscovy ducks comprising 287 males and 733 females. These birds were randomly sampled from Rain Forest, Derived Savanna and Guinea Savanna agro-ecological zones of Nigeria. Sex significantly (P < 0.001) affected all morphometric measurements in favour of males. Assessment of relative contribution of morphological traits to SSD through SDI and SSDI revealed that body weight followed by skeletal frame-related variables (body length and wing length) were the most dimorphic traits. Three Principal Components were generated for each sex; accounting for 62.70 % and 54.24 % of the total variance explained of male and female ducks, respectively. In tandem with the SDI and SSDI results, Stepwise Discriminant analysis indicated body weight as the best predictor of sex of adult Muscovy ducks followed by wing length and body length; correctly classifying 98.5 % of ducks and are reliable for sex determination in the field. The established SSD in this study could be employed for description, utilization, selection and planning of improvement programs of male and female Muscovy ducks.